Osada kultury łużyckiej w Rychłowicach, gm. Wieluń, woj. sieradzkie, stan. 1 - Janiak, Radosław (Acta Universitatis Lodziensis. Folia Archaeologica, 1998)
Rychłowice, site 1 is situated about 3 km to the south of Wieluń between Rychłowice and Nowy Świat valley. It is on the high hill which was partially destroyed due to gravel exploration there. Two seasons of rescue excavations uncovered 26 settlement pits. Five of them served domestic needs, one possessed a fire place, the other a fire place and postpits around it. Seventeen of them were farming structures. Four pits are difficult to be qualified for either group. The pottery assemblage consists of two-conical, and vase-like vessels, amphoras, egg-like pots, mugs, scoopers, bowls and plates. Bronze artefacts are worth mentioning, namely a little spearhead, ring and ear-ring. Pottery forms of Rychłowice and their ornamentation classify the site to the fifth period of Bronze Age (900-700 BC acc. to O. Montelius). At the site there appeared pottery material characteristic for Kępno undergroup of the Upper-Silesian-Little Poland Lusatian culture.